The history of pellagra - Jaworek, Andrzej K.; Łazarczyk, Agnieszka; Hałubiec, Przemysław; Leończyk, Monika; Staszewski, Filip; Wojas-Pelc, Anna (Dermatology Review/Przegląd Dermatologiczny, 2021)
Currently pellagra is usually the subject of dermatological or non-dermatological case reports. Since the first description of the disease, its cause has remained unknown for many years. There were no known methods of prevention and treatment. For two centuries, pellagra was an incurable disease and caused several hundred thousand deaths in Europe and North America. Research by clinicians and scientists has made it possible to refute the common theory of the infectious etiology of the disease and link the disease epidemic to maize, which was then the primary source of food for the poor. Consumption limited to this grain resulted in an extreme deficiency of niacin (vitamin B3) and symptoms of pellagra. Niacin supplementation caused the lesions to regress, and became crucial to combat the epidemic. The article presents the first descriptions, the greatest outbreaks of the epidemic and the stormy process of discovering data on the etiology of pellagra, as well as typical clinical features of the diseases.